Comparison of widefield swept-source optical coherence tomography angiography and ultra-widefield fluorescein angiography in the detection of non-perfusion areas in diabetic retinopathy - Guo, Chuyun; Xiao, Ning; Li, Fang; Han, Yue; Chen, Li; Chen, Hongzhuang; Shen, Yadan; Ning, Xinru; Ling, Ruolan; Wang, Xi; Zhang, Lin; Wang, You; et al. (Frontiers in Endocrinology, 2025)
PurposeTo compare the detection of non-perfusion areas (NPAs) in diabetic retinopathy (DR) using 24×20 mm widefield swept-source optical coherence tomography angiography (SS-OCTA) and ultra-widefield fluorescein angiography (UWFA), and to explore NPA distribution patterns.MethodsThis retrospective study included 64 eyes from 48 DR patients who underwent 24×20 mm SS-OCTA and UWFA examinations. NPAs were manually annotated, and the detection rates and distribution patterns across retinal quadrants were analyzed and compared between the two imaging modalities.ResultsCompared to UWFA, the 24×20 mm SS-OCTA scan range missed 53.40% of total NPAs. The detection rates within the SS-OCTA scan range varied across quadrants: 50.58% (superior temporal), 55.33% (inferior temporal), 43.99% (superior nasal), and 43.45% (inferior nasal). NPAs were most prevalent in the inferior nasal region (40.16% of total NPAs). The ischemic index (ISI) derived independently from NPAs identified by the two imaging modalities showed a very strong positive correlation.ConclusionsWithin the scan range of 24×20 mm SS-OCTA, over 50% of total NPAs were missed compared to UWFA. However, OCTA can accurately reveal the degree of retinal ischemia within its field of view. NPA is unevenly distributed in the retina, with the predominant area being the inferior nasal region. This study suggests that this area should be prioritized for assessment in DR management.